Serum Levels of Granulocyte-Macrophage-colony-stimulating Factor and Stem-cell Factor During Liver Regeneration after Partial Hepatectomy in Humans - Fiume, Diego; Lenci, Ilaria; Milana, Martina; Manzia, Tommaso M.; Massoud, Renato; Tariciotti, Laura; Russo, Carmelo; Toti, Luca; Baiocchi, Leonardo (Reviews on Recent Clinical Trials, 2020)
Background: Multiple biological functions have been recognized regarding Granulocyte Macrophage-Colony Stimulating Factor (GM-CSF) and Stem Cell Factor (SCF). Aim: To evaluate the serum changes of GM-CSF and SCF in patients undergoing surgical resection for liver tumor, in the regenerative phase after surgery in order to identify the possible relationship with the patient, tumor or surgical variables. Methods: Thirty-two consecutive patients (50% male, median age 66), undergoing hepatic resection of liver neoplasm, were evaluated. The liver tumor was Hepatocellular Carcinoma (HCC) in 44% of cases. Other tumors were cholangiocarcinoma and metastasis. Serum levels of GM-CSF and SCF were assessed at baseline and 2 days, 7 days and 4 weeks after surgery. Personal and clinical patient data were also recorded. The statistical analysis was carried out using t-test for unpaired data or ANOVA (repeated measure) for continuous variables and Fisher test for discrete variables. Results: GM-CSF levels remained constant after surgery and were compared to baseline values. SCF levels, on the other hand, increased during the time, after surgery. The evaluation of SCF levels (fold increase) according to surgical, patient and tumor variables evidenced some differences. At day 7 and week 4, SCF levels were statistically increased: i) in patients undergoing a large resection in comparison with others (p<0.05); ii) in patients non-cirrhotic in comparison with cirrhotic ones (p=0.02) and finally; iii) in patients with non-HCC tumor in comparison with HCC ones (p=0.02). Conclusion: During liver regeneration in humans, SCF serum levels are increased allowing to hypothesize a possible role of this chemokine during tissue growth and remodeling.
Keywords: liver resection